2020
DOI: 10.1021/acs.joc.0c01300
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Povarov Reaction in Biaryls under Iron Catalysis for the General Synthesis of Dibenzo[a,c]Acridines

Abstract: A modified Povarov reaction involving 2′-alkynylbiaryl-2-carbaldehydes and aryl amines with tandem oxidation was performed using catalytic FeCl 3 . The outcome was an efficient general synthesis of dibenzo[a,c]acridines with moderate to high yields. This method offers simplicity in the preparation of substrates, diverse substrate scope, and high atom economy. The generality of the protocol was verified by synthesizing a tribenzo[a,c,h]acridine derivative. Photophysical properties of the synthesized compounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…For example, Hashmi and co-workers reported in 2018 a -extending strategy towards dibenzo[a,c]acridines using gold-catalysis for C-H annulation of 2-ethynylbiaryls with anthranils. 16 We can also cite the modified iron-catalysed Povarov reaction involving 2-(2'-alkynylaryl)benzaldehydes and arylamines documented by Jana and co-workers in 2020 to access the same scaffolds 17 (Figure 2). 16,17 We recently showed that substrates such as 2aminobenzaldehyde 18 and 2-aminophenones 19 could be converted into either acridines, by N-arylation and subsequent cyclization, or acridones, by double N-arylation followed by cyclization.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, Hashmi and co-workers reported in 2018 a -extending strategy towards dibenzo[a,c]acridines using gold-catalysis for C-H annulation of 2-ethynylbiaryls with anthranils. 16 We can also cite the modified iron-catalysed Povarov reaction involving 2-(2'-alkynylaryl)benzaldehydes and arylamines documented by Jana and co-workers in 2020 to access the same scaffolds 17 (Figure 2). 16,17 We recently showed that substrates such as 2aminobenzaldehyde 18 and 2-aminophenones 19 could be converted into either acridines, by N-arylation and subsequent cyclization, or acridones, by double N-arylation followed by cyclization.…”
Section: Introductionmentioning
confidence: 95%
“…16 We can also cite the modified iron-catalysed Povarov reaction involving 2-(2'-alkynylaryl)benzaldehydes and arylamines documented by Jana and co-workers in 2020 to access the same scaffolds 17 (Figure 2). 16,17 We recently showed that substrates such as 2aminobenzaldehyde 18 and 2-aminophenones 19 could be converted into either acridines, by N-arylation and subsequent cyclization, or acridones, by double N-arylation followed by cyclization. Inspired by these results, we here report how similar anilines can react with 2iodotriphenylene in order to deliver new PAHs based on acridine or acridone for which the photophysical properties were studied.…”
Section: Introductionmentioning
confidence: 95%
“…Aqueous ethanol possesses various attractive advantages, such as nonvolatility, recyclability, easy operation, and low cost. There are several reports about the applications of aqueous ethanol in organic reactions such as Diels-alder reaction [31], dehydrobromination-rearrangement, thermal electro-cyclizations [32], Hantzsch reaction [33], Claisen Schmidt condensation [34], N-Mannich base reaction [35], and Biginelli reaction [36]. In this present work, we have proposed a new synthetic method for the access of novel 3,3-dimethyl-3,4-dihydro-1H-spiro[acridine-9,3 0indoline]-1,2 0 (2H,10H)-diones derivatives under catalystfree conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The key step to approach the dibenzo[f,h]quinoline scaffold include the Skraup synthesis 9d,10 and various cyclization 11 and cross-coupling reactions 12 catalyzed by transition metals such as nickel, 13 palladium, 14 gold, 15 or iron. 16 Some recently reported synthetic approaches towards the syntheses of dibenzo [f,h]quinolones are shown in Figure 1. Zhang and co-workers developed a palladium-catalyzed double cross-coupling reaction between cyclic diaryliodonium salts and 2-chloropyridinyl acids to access dibenzo-[f,h]quinolines and their derivatives (Figure 1a).…”
mentioning
confidence: 99%
“…The key step to approach the dibenzo[ f , h ]quinoline scaffold include the Skraup synthesis 9d 10 and various cyclization 11 and cross-coupling reactions 12 catalyzed by transition metals such as nickel, 13 palladium, 14 gold, 15 or iron. 16…”
mentioning
confidence: 99%